Monetary and Fiscal Management: Framework and Evidences - Basyal, Tula Raj (Economic Journal of Nepal, 2006)
Macroeconomic management should contribute to higher economic growth without disturbing the macroeconomic stability, which is essential for attaining sustained higher level of economic growth. Sound macroeconomic management would also improve the external sector competitiveness of the economy on a sustainable basis, a precondition for reducing the external sector vulnerability of the economy. Balance of payments crises and foreign debt problems are often caused and aggravated by imprudent fiscal policy the solution of which would involve some combination of cutting public spending and raising additional revenue, thereby freeing resources for export and debt servicing. With increased fiscal expansion or fiscal deficit, current account deficit widens and the level of government debt in proportion to GDP increases accordingly. Unsustainable fiscal deficit would encourage capital flight which would deteriorate the debt problem. Monetary policy seeks to regulate money supply and thereby liquidity by changing the availability and cost of credit for influencing the volume of aggregate demand in the economy and, therefore, inflation. The usual expansionary impact of fiscal policy is offset by a rise in the value of the currency. Under fixed exchange rates, only fiscal policy can affect income. The normal potency of monetary policy is lost because the money supply is dedicated to maintaining the exchange rate at the announced fixed level. Only a system of floating exchange rates leaves monetary policy free to pursue other goals, such as employment or prices. As the most important instrument in implementing the monetary policy, the central bank buys or sells government securities, which affects the level of liquidity and short-term interest rates that prompt the banks to let their reserves grow at a level consistent with the objectives of monetary policy. It can be expected that the role of the monetary policy to contribute to create sound macroeconomic fundamentals and foster sustained economic growth through increased emphasis on the secondary market operation will remain potent in the days to come.Economic Journal of Nepal Vol.29(2) 2006 pp.63-76